Social Media as a Seed of Connective Democracy in Myanmar (Burma): Freedom of Speech, Contractarianism, and Strategic Use of Social Media - Do Kyun David Kim; Isaac Kim (Social Media + Society)
In the era of digital communication, social media have often been considered a bastion of freedom of speech, both at national and global levels. However, in Myanmar, the military government has imposed strict control over social media since its coup in 2021, while using them to disseminate authoritarian propaganda. Civilians who have voiced opposition against the regime have been arrested, and foreign media networks have withdrawn their operations from the country due to governmental oppression. Recognizing the oppressive political climate and its impact on freedom of speech and public discourse on social media, this study aims to achieve two objectives: (1) constructing a theoretical model of connective democracy for Myanmar by integrating the concepts of freedom of speech and contractarianism, and (2) suggesting effective strategic social media communication strategies to liberate Myanmar. These theoretical and practical approaches will contribute to constructing connective democracy not only in Myanmar but also other countries under political oppression and communication censorship.